2008
DOI: 10.1177/1469605307086079
|View full text |Cite
|
Sign up to set email alerts
|

Mortuary practices in Bam after the earthquake

Abstract: On 26 December 2003, an earthquake in Bam, south-eastern Iran, resulted in an estimated death toll of 40,000. This article suggests that post-disaster burial practices provide alternative avenues for research, notably the changes in burial styles, grave markers and other material culture associated with burials. This article is the result of ethnoarchaeological research conducted on eight cemeteries in Bam, at intervals of 2, 6 and 17 months after the earthquake. The cemeteries chosen span a time period of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Our research agenda was focused on investigating five central themes in relation to Bam and the 2003 earthquake: population change, material culture, graveyards, markets, and domestic architecture. In this article I discuss some of these themes (see also Garazhian and Papoli Yazdi 2008). The overriding goal of the Project was to apprehend the gradual process through which Bam residents were returning to normal ways of life.…”
Section: The Bam Ethnoarchaeology Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research agenda was focused on investigating five central themes in relation to Bam and the 2003 earthquake: population change, material culture, graveyards, markets, and domestic architecture. In this article I discuss some of these themes (see also Garazhian and Papoli Yazdi 2008). The overriding goal of the Project was to apprehend the gradual process through which Bam residents were returning to normal ways of life.…”
Section: The Bam Ethnoarchaeology Projectmentioning
confidence: 99%
“…In the first few weeks following the earthquake, many survivors buried their loved ones and then left the city (Garazhian and Papoli Yazdi 2008). After about 2 months though, many returned to the rubble piles that were previously their homes.…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis in Bam in Southeast Iran following the 2003 earthquake found that whilst many changes in funerary practice occurred 1-6 months after the earthquake, these changes were being abandoned as normality was restored 17 months later. Garazhian and Yazdi (2008) suggest that if such short-term changes were observed in the archaeological record, they may represent the effects of disasters. Ethnoarchaeology can also be used to investigate issues such as kinship, social and political organisation, symbolism and ritual (Parker Pearson, 1999;Thomas and Kelly, 2006;Verhoeven, 2009).…”
Section: An Overview Of Ethnoarchaeologymentioning
confidence: 99%
“…Downes (1999) then discusses generic Bronze Age cremation in comparison with the Balinese Thomas and Kelly (2006, p. 74). cremation, finding the concepts of the journey of the deceased and transformation to be important in both cultures. Garazhian and Yazdi (2008) have used ethnoarchaeology to study the consequences for funerary ritual in times of social change and abandonment in response to disaster. Their analysis in Bam in Southeast Iran following the 2003 earthquake found that whilst many changes in funerary practice occurred 1-6 months after the earthquake, these changes were being abandoned as normality was restored 17 months later.…”
Section: An Overview Of Ethnoarchaeologymentioning
confidence: 99%
“…An official number of 31,500-31,828 was later established (Berberian 2014). In addition, between 17,500 and 50,000 people suffered injuries Berberian 2005;Garazhian and Papoli Yazdi 2008;Berberian 2014). Details about the death toll in various organizations and educational and health institutions in Bam are offered by Parsizadeh and Izadkhah (2005) and Berberian (2014).…”
Section: Lessons and ''Lessons Learned'' From The Rudbar 1990 Earthqumentioning
confidence: 99%